Radio and optical observations of the possible AE Aqr twin, LAMOST J024048.51+195226.9. Issue 3 (20th February 2021) - Pretorius, M L; Hewitt, D M; Woudt, P A; Fender, R P; Heywood, I; Knigge, C; Miller-Jones, J C A; Buckley, D A H; Worters, H L; Potter, S B; Williams, D R A
ABSTRACT: It was recently proposed that the cataclysmic variable (CV) LAMOST J024048.51+195226.9 may be a twin to the unique magnetic propeller system AE Aqr. If this is the case, two predictions are that it should display a short period white dwarf spin modulation, and that it should be a bright radio source. We obtained follow-up optical and radio observations of this CV, in order to see if this holds true. Our optical high-speed photometry does not reveal a white dwarf spin signal, but lacks the sensitivity to detect a modulation similar to the 33 s spin signal seen in AE Aqr. We detect the source in the radio, and measure a radio luminosity similar to that of AE Aqr and close to the highest so far reported for a CV. We also find good evidence for radio variability on a time-scale of tens of minutes. Optical polarimetric observations produce no detection of linear or circular polarization. While we are not able to provide compelling evidence, our observations are all consistent with this object being a propeller system.